La gobernanza ambiental en el Perú. Aspectos fundamentales para la gestión del agua - Tassano Velaochaga, Hebert (2024)
This research aims to conceptualize governance as part of a crucial institu tional transformation process to address environmental challenges. In this context, a specific focus on water management and its relationship with in tegrated water resources management is highlighted. Furthermore, the need for water resources administration, led by the National Water Authority, to evolve towards an inclusive approach that strengthens institutions and, con sequently, environmental governance is emphasized. Finally, it is concluded that strengthening institutions is fundamental to improving governance, with a special emphasis on new water management regulations.